1987
DOI: 10.1038/327155a0
|View full text |Cite
|
Sign up to set email alerts
|

Substance P-immunoreactive retinal ganglion cells and their central axon terminals in the rabbit

Abstract: Retinal ganglion cells are the projection neurons that link the retina to the brain. Peptide immunoreactive cells in the ganglion cell layer (GCL) of the mammalian retina have been noted but their identity has not been determined. We now report that, in the rabbit, 25-35% of all retinal ganglion cells contain substance P-like (SP) immunoreactivity. They were identified by either retrograde transport of fluorescent tracers injected into the superior colliculus, or by retrograde degeneration after optic nerve se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 22 publications
11
72
1
Order By: Relevance
“…Both of these methods, however, are subject to error, since it is difficult to determine that all ganglion cells degenerate after axotomy or transport HRP retrogradely. Our analysis of the GCL of the rabbit retina employed both of these experimental approaches (32,33). The distribution and density of neurons in the GCL after optic nerve transection and extended survival periods (32) are in close agreement with the pattern and density of neurons that did not contain HRP reaction product after multiple injections of this enzyme into the superior colliculus (33).…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Both of these methods, however, are subject to error, since it is difficult to determine that all ganglion cells degenerate after axotomy or transport HRP retrogradely. Our analysis of the GCL of the rabbit retina employed both of these experimental approaches (32,33). The distribution and density of neurons in the GCL after optic nerve transection and extended survival periods (32) are in close agreement with the pattern and density of neurons that did not contain HRP reaction product after multiple injections of this enzyme into the superior colliculus (33).…”
Section: Resultsmentioning
confidence: 51%
“…A smaller number of lightly stained medium-to large-size cell bodies, encountered most frequently in central retinal regions, were also observed. In retinas whose optic nerve was transected, and after a survival period sufficiently long to eliminate most ganglion cells (9,32), there was no change in the number of small GABA-ir cells in the GCL, but there was a substantial reduction in the number of mediumto large-size GABA-ir cells. These observations suggest that (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not observe NT-labeled ganglion cells projecting to the pigeon nBOR in a recent study (Britto etal., 1988). Substance P has been shown to occur in the retinal projection to the rabbit AOS (Brecha et al, 1987) and in the retinal projection to the tectal system in both anurans (Kuljis & Karten, 1983 and chickens (Ehrlich et al, 1987). The presence of SP-positive fibers has been reported in the AOS in a mapping study of the turtle brain, although the SP-positive fibers were restricted to a region that appears equivalent only to the avian nBORd (Reiner et al, 1984).…”
Section: Classical Transmitters and Receptorsmentioning
confidence: 96%
“…There appear to be only three reports on putative transmitters in the ganglion cells projecting to the AOS. The first indicates the occurrence of substance P-like immunoreactivity in such cells in the rabbit (Brecha et al, 1987). The second demonstrated that approximately 10% of the displaced retinal ganglion cells projecting upon the pigeon accessory optic nucleus exhibit tyrosine hydroxylase-like immunoreactivity .…”
Section: Introductionmentioning
confidence: 99%